Publishing trends in economics across colleges and universities, 1991 - 2007 - Anne E. Winkler; Sharon G. Levin; Paula E. Stephan; Wolfgang Glänzel (Institute for the Study of Labor (IZA), 2011)
There is good reason to think that non-elite programs in economics may be producing relatively more research than in the past: Research expectations have been ramped-up at non-PhD institutions and new information technologies have changed the way academic knowledge is produced and exchanged. This study investigates this question by examining publishing productivity in economics (and business) using data from the Web of Science (Knowledge) for a broad set of institutions both elite and non-elite over a 17-year period, from 1991 through 2007. Institutions are grouped into six tiers using a variety of sources. The analysis provides evidence that non-elite institutions are gaining on their more elite counterparts, but the magnitude of the gains are small. Thus, the story is more of constancy than of change, even in the face of changing technology and rising research expectations.
urn:nbn:de:101:1-201111213034
Keywords: A14; I23; 330; higher education; research productivity; publishing trends; inequality; Wirtschaftswissenschaft; Wirtschaftshochschule; Bibliometrie; Welt